Is leadership in the eyes of the beholder: a study of intended and perceived leadership practices and organizational performance - Jacobsen, Christian Botcher; Andersen, Lotte Bogh (2015)
Leadership is a matter of both intentions and perceptions, which do not necessarily always match. Because employees motivation and commitment are only affected by leadership if they notice it, employee-perceived leadership is expected to have a stronger correlation with organizational performance than leader-intended leadership. This expectation is tested for transformational and transactional leadership, as both types of practices are expected to increase performance. Using a sample of 1,621 teachers and 79 Danish high school principals, the authors find that leader-intended and employee-perceived transformational and transactional leadership are only weakly correlated and that only employee-perceived leadership practices (both transformational and transactional) are significantly related to objectively measured school performance. The results show that it is important to distinguish between intended and perceived leadership and that leaders should be aware of how their practices are perceived. - Reproduced.
Keywords: Organizations; Leadership